Techniques for Optimizing Acetabular Component Positioning in Total Hip Arthroplasty: Defining a Patient-Specific Functional Safe Zone. Issue 2 (February 2019) - Feng, James E.; Anoushiravani, Afshin A.; Eftekhary, Nima; Wiznia, Daniel; Schwarzkopf, Ran; Vigdorchik, Jonathan M.
Abstract : Proper acetabular component positioning is dependent on multiple factors. Proper preoperative templating is of utmost importance, and the surgeon must take care to determine acetabular position and location, orientation (anteversion and inclination), and size, while also focusing on limb length and offset. Patient positioning on the operative table, whether in the supine or lateral position, can affect final acetabular component position. Intraoperative execution with use of appropriate tools and techniques (e.g., anatomical landmarks, mechanical alignment guides, and computer-assisted or robotic navigation) allows for component positioning consistent with the preoperative plan. It is important to understand the benefits and limitations of each tool, recognizing how to identify and remove the possibility of error.